African American women's preventative care usage: the role of social support and racial experiences and attitudes. Issue 7 (21st April 2014) - Pullen, Erin; Perry, Brea; Oser, Carrie
Abstract Research suggests that African Americans are less likely to utilise preventative care services than Americans of European descent, and that these patterns may contribute to racial health disparities in the United States. Despite the persistence of inequalities in preventative care utilisation, culturally relevant factors influencing the use of these gateway health services have been understudied among marginalised groups. Using a stratified sample of 205 low‐income African American women, this research examines the predictors of receiving a physical exam, with a particular emphasis on how differing levels of social support from friend and family networks and experiences of racial discrimination and cultural mistrust shape utilisation. The findings underscore the importance of traditional predictors of utilisation, including insurance status and having a usual physician. However, they also indicate that supportive ties to friendship networks are associated with higher predicted rates of having an annual physical exam, while social support from family and sentiments of cultural mistrust are associated with lower rates of utilisation. Broadly, the findings indicate that even as traditional predictors of help‐seeking become less relevant, it will be critical to explore how variations in discrimination experiences and social relationships across marginalised groups drive patterns of preventative care utilisation.